The Effectiveness of the Guided Discovery Learning Model and Project-Based Learning in the Digital Beauty Design Course - Yanita, Merita; Husni, Rafikah; Jalinus, Nizwardi; Ridwan (AI Society & STMIK Indonesia, 2023)
This study aims to look at the effectiveness of the Guided Discovery Learning (GDL) learning model and the Project-Based Learning (PjBL) model in terms of learning achievement, self-confidence, and students' critical thinking skills in the Digital Beauty Design course. This type of research is Quasi experiment. The subjects of this study were two classes of students from the Department of Cosmetology and Beauty Education, Padang State University who were randomly selected. Data analysis to test the effectiveness of the GDL model and PjBL model in terms of each dependent variable using the t test. While the data analysis technique to test the difference between the effectiveness of the GDL model and the PjBL model uses the MANOVA test. The results showed that, in terms of learning achievement, self-confidence, and students' critical thinking skills, it is known that the application of the GDL model in the Digital Beauty Design course is effective, the application of the PjBL Model in the Digital Beauty Design course is effective, and there is no difference in the effectiveness of the GDL model and the PjBL model. in the Digital Beauty Design course.